Enforcement for road safety in Oman: Evidences from the road safety research program in Oman - Abdulla Almaniri (19794501) (2015)
Oman has undergone a rapid epidemiological transition, and has witnessed substantial social and economic changes in the last four decades. Based on oil revenues, the government of Oman has accelerated the development, in the present context, of road network and rapid growth of motorization. Despite the positive side of the substantial development, however, there are other challenges appeared on the scene that have negative impacts. Today, road traffic crashes, injuries and fatalities are a public health challenge in Oman in terms of immeasurable human suffering along with the huge economic and social costs incurred as well as becoming a burden on health sector i.e. main external cause of morbidity, particularly among young and adults. Oman presents a fertile ground to explore the contributory factors of road traffic crashes and their consequences of injuries and fatalities. Recognizing the importance of research to understand road traffic injuries and provide effective interventions, The Research Council initiated a strategic program for road safety research within Oman in April 2010, the Road Safety Research Program (RSRP). The main objective of the RSRP is to promote scientific research and build national capacity in road safety research for the purpose of supporting decision makers in implementing evidence-based solutions to combat road traffic injuries in the Sultanate of Oman. The RSRP has operated on the basis of competitive and commissioned research grants as means to promote innovative research projects that would have a direct bearing on reducing the burden of road traffic injuries (RTI) in Oman. This presentation will highlight major projects funded within the RSRP that address low enforcement and traffic policing as a major intervention for road safety. In particular, this presentation will present findings from projects exploring traffic policing in Oman, evaluation of the deterrence practices for heavy vehicle safety, and traffic enforcement for novice driver safety. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.71